Pengaruh Kesadaran, Dan Pengetahuan Perpajakan Terhadap Tingkat Kepatuhan Wajib Pajak Umkm Tahun 2020 (Studi Kasus Pada KPP Pratama Jakarta Tebet) - Muhammad Alfian Hendrawan; Ajat Sudrajat (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study was conducted to determine the effect of tax awareness and knowledge on the compliance level of MSME taxpayers in 2020 the area of the Primary Tax Office of Tebet, Jakarta. MSME taxpayer compliance is still considered low. Tax awareness and knowledge are important factors for evaluating the compliance of MSME taxpayers registered at the Primary Tax Office of Tebet, Jakarta. This research is a descriptive quantitative research with data collection method of questionnaire distribution. A sample consisting of 70 respondents was taken using accidental sampling technique. The data obtained were processed using SPSS version 24 and analyzed statistically. The data analysis technique used was multiple linear regression analysis. The research results show that the sig value of tax awareness is 0.00 < 0.05 and the sig value of tax knowledge is 0.01 < 0.05 which indicates that tax awareness has a partial effect on MSME taxpayer compliance and tax knowledge has a partial effect on MSME taxpayer compliance. Simultaneously the influence of the tax awareness and tax knowledge variables on the level of compliance of MSME taxpayers at the Primary Tax Office of Tebet, Jakarta is 53%, with the remaining 47% being the influence of other variables outside the model studied.